2009
DOI: 10.1080/02827580902773470
|View full text |Cite
|
Sign up to set email alerts
|

Variation in spring and autumn frost tolerance among provenances of Russian larches (Larix Mill.)

Abstract: Spring and autumn frost tolerance was measured using material from a range-wide (50Á678 N, 38Á1588 E) provenance trial of four Russian larch species (Larix sukaczewii Dyl., L. sibirica Ledeb., L. gmelinii Rupr. and L. cajanderi Mayr.) growing in northern Sweden. Shoots were collected in early May and late September and frozen at (8, (12, (16 and (208C. Cambial damage was assessed visually after development under ideal conditions for 2 weeks. Differences in frost damage among provenances were highly significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…In an arti-ficial freezing test with similar study material, Eysteinsson et al (2009) found highly significant differences in frost damages. Furthermore, they found a correlation between autumn frost damage and provenance latitude and longitude, as well as one between spring frost damage and longitude.…”
Section: Damagesmentioning
confidence: 99%
See 1 more Smart Citation
“…In an arti-ficial freezing test with similar study material, Eysteinsson et al (2009) found highly significant differences in frost damages. Furthermore, they found a correlation between autumn frost damage and provenance latitude and longitude, as well as one between spring frost damage and longitude.…”
Section: Damagesmentioning
confidence: 99%
“…When the three provenances from Altai Mountains were excluded from the analysis, altitude was no longer a significant variable (p > 0.05); instead longitude had significant negative correlation with frost damages in Punkaharju, and Dahurian larches had less frost damages. Eysteinsson et al (2009) found that provenances from Magadan had high levels of both spring and autumn frost damages. In Kivalo, 13A Magadan had the highest number of frost damages, but in Punkaharju damages were below average.…”
Section: Damagesmentioning
confidence: 99%
“…However, parameters derived at specific sites are often inferior to multi-site parametrizations at sites other than those where they have been obtained (Figure 4). Hence, site-specific calibration is particularly suitable to address responses to current climate conditions but should be used with caution if acclimation processes to local biotic and abiotic conditions are expected [20,21,26,116,117]. For example, the inter-site differences for model parameters involved for photosynthetic activity i.e., AMAXB, PSNTOPT, between boreal and temperate pine forests are large.…”
Section: Site-specific Versus Multi-site (Species-specific) Parametrimentioning
confidence: 99%
“…Firstly, the level of process description does not allow for sufficient model sensitivity to changing environmental conditions, and secondly, genetic acclimation of species to surrounding ecosystem properties may substantially vary with the geographical range [19][20][21]. Genetic differentiation and adaptation to local environmental conditions is a common phenomenon and has been reported for pine [22], spruce [23] beech [24] and other species [21,25,26]. Assuming a sufficient degree of complexity in process description, model parameter calibration to individual ecosystems (site-specific) might be able to address the response of stand acclimation to local biotic and abiotic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Eysteinsson et al (2009) described the genus Larix as frequently being injured by winter and spring frosts; however, different species differ in frost resistance, and the least resistant trees were from the far-east provenances. Young Larix decidua trees are commonly destroyed by frost in the northern provinces of Europe (Carswell & Morgenstern, 1995;Karlman & Karlsson, 2013) because a lower cumulative temperature is necessary to trigger bud development (Eriksson et al, 2006).…”
Section: Site Effectsmentioning
confidence: 99%